The challenge of the '80s Congress of Civil Engineers programme, Edinburgh 1-4 April 1982. (Thomas Telford, 1982)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of second congress of civil engineers held in Edinburgh on 1-4 April 1982.
Keywords: Engineering -- Study and teaching (Higher) -- Great Britain -- Congresses.; elektronické knihy; electronic books